Optimisation of remotely-pumped EDFA location for unrepeatered transmission systems - Abidin, M.S.Z.; Naji, A.W.; Al-Mansoori, M.H.; Adikan, Faisal Rafiq Mahamd; Mahdi, M.A. (2007)
In this paper, a new technique of determining the location of a remotely-pumped Erbium doped fibre amplifier (R-EDFA) in unrepeatered transmission system is presented. The location of the R-EDFA is varied over the transmission span with its optimised pump power. The unrepeatered transmission link is optimised when the R-EDFA is located closer to the receiver end.